2013
DOI: 10.1016/j.wear.2013.03.049
|View full text |Cite
|
Sign up to set email alerts
|

Self-mated tribological systems based on multilayer micro/nanocrystalline CVD diamond coatings

Abstract: The tribological response of multilayer micro/nanocrystalline diamond coatings grown by the hot filament CVD technique is investigated. These multigrade systems were tailored to comprise a starting microcrystalline diamond (MCD) layer with high adhesion to a silicon nitride (Si3N4) ceramic substrate, and a top nanocrystalline diamond (NCD) layer with reduced surface roughness. Tribological tests were carried out with a reciprocating sliding configuration without lubrication. Such composite coatings exhibit a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…The free surfaces of the coatings (Figure 2a,b) present clusters of nanosized diamond particles without any crystalline facets as described for similar diamond multi-layered coatings [18]. The cross-sections obtained by fracture (Figure 2c,d) depict the multi-layered structure of the coatings, the MCD layers being much thinner than NCD.…”
Section: Multilayer Mcd/ncd Coatingsmentioning
confidence: 59%
See 1 more Smart Citation
“…The free surfaces of the coatings (Figure 2a,b) present clusters of nanosized diamond particles without any crystalline facets as described for similar diamond multi-layered coatings [18]. The cross-sections obtained by fracture (Figure 2c,d) depict the multi-layered structure of the coatings, the MCD layers being much thinner than NCD.…”
Section: Multilayer Mcd/ncd Coatingsmentioning
confidence: 59%
“…This coating architecture relies on the strong adhesion of a first layer of MCD to the plasma etched Si 3 N 4 ceramic substrate [22] and on the insertion of intermediate MCD layers creating MCD/NCD interfaces that act as energy sinks to crack propagation [19]. The top layer is of NCD to ensure a smoother surface, R a (ML10x1) = 79 ± 7 nm and R a (ML10x2) = 145 ± 6 nm, relatively to uncoated, etched substrates, or to substrates coated solely with MCD [18]. Thick NCD layers combined with thin MCD layers act in a way that further contributes to reduce the surface roughness of the tools.…”
Section: Multilayer Mcd/ncd Coatingsmentioning
confidence: 99%
“…In fact, several works on the tribological behaviour of NCD-on-NCD contacts have been demonstrated the excellence of this tribopair [3][4][5][6][7]. Following a short-time running-in period where the protruding nanodiamond asperities suffer from truncation and blunting, the NCD-on-NCD sliding system attains a steady-state friction regime with very low friction coefficients (0.01-0.05), characteristic of highly polished passivated surfaces [4][5][6][7]. A very mild wear regime is in line with this friction response, with low wear coefficient values in the range of 10 -9 mm 3 ⋅N -1 ⋅m -1 for water lubricated contacts [5] and one order of magnitude higher for dry systems [4].…”
Section: Introductionmentioning
confidence: 99%
“…These morphological and topographic characteristics, together with diamond´s extreme hardness and chemical inertness, are key factors for the application of NCD coatings in tribology. In fact, several works on the tribological behaviour of NCD-on-NCD contacts have been demonstrated the excellence of this tribopair [3][4][5][6][7]. Following a short-time running-in period where the protruding nanodiamond asperities suffer from truncation and blunting, the NCD-on-NCD sliding system attains a steady-state friction regime with very low friction coefficients (0.01-0.05), characteristic of highly polished passivated surfaces [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Dumpala et al have reported that nanocrystalline diamond layer was deposited over microcrystalline diamond layer with a coating architecture of NCD/ transition layer/MCD/WC-Co using hot filament chemical vapour deposition technique (HFCVD), and the graded transition layer was realized by controlling methane concentration and chamber pressure in order to integrate the MCD and NCD layers [12]. Salgueiredo et al have also reported that multilayer micro/nanocrystalline diamond coatings can be obtained by controlling the methane concentration and using the HFCVD technique [13]. Additionally, Dumpala investigated the nanocrystalline diamond coatings deviated from the nanocrystallinity with increasing thickness and exhibited the surface characteristics of microcrystalline diamond [14].…”
Section: Introductionmentioning
confidence: 99%